The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/6265183
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Transcatheter Arterial Embolization to Treat Renal Hemorrhage after Percutaneous Nephrolithotomy

Abstract: Purpose. The aim of this study was to evaluate the safety and efficacy of transcatheter arterial embolization (TAE) in patients with renal hemorrhage after percutaneous nephrolithotomy (PCNL) and evaluate the risk factors that may result in severe bleeding requiring TAE. Methods. We retrospectively reviewed 121 patients with post-PCNL renal hemorrhage. Thirty-two patients receiving endovascular embolization were compared with 89 patients only receiving conservative treatment. The demographic and clinical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…This agreed with Limtrakul et al who reported clinical success of 91.5% for their 94 patients treated with RAE [17]. Moreover, Du et al reported clinical success of 100% of RAE compared to conservative therapy that was 73.6% in their cases of bleeding after PCNL [18]. Regarding treatment failure, RAE failed to control bleeding in 3 cases of our patients.…”
Section: Discussionsupporting
confidence: 90%
“…This agreed with Limtrakul et al who reported clinical success of 91.5% for their 94 patients treated with RAE [17]. Moreover, Du et al reported clinical success of 100% of RAE compared to conservative therapy that was 73.6% in their cases of bleeding after PCNL [18]. Regarding treatment failure, RAE failed to control bleeding in 3 cases of our patients.…”
Section: Discussionsupporting
confidence: 90%
“…Currently, SRAE has become a recognized treatment for severe and persistent renal bleeding after PCNL that fails to achieve a satisfactory outcome through conservative treatment (1,19). The technical and clinical success rates of embolization for renal hemorrhage have been reported to be 87-100% and 57-100%, respectively (18).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we retrospectively evaluated the safety and efficacy of SRAE in the treatment of hemorrhage after PCNL. In addition, although renal artery embolization has been regarded as the treatment of choice for postoperative bleeding of PCNL (18)(19)(20), there are still reports of recurrent hemorrhage after embolization (1, 7), and even Mao et al reported that up to 17.3% of patients experienced initial treatment failure and underwent repeat SRAE (16). The failure of embolization may be partly due to immature embolization techniques and improper selection of embolization materials.…”
Section: Introductionmentioning
confidence: 99%
“…In most patients, bleeding after the procedures is controlled by conservative treatment, but severe bleeding requires emergency management. The risk factors for severe bleeding are huge stones, lower puncture site, number and type of stones, operative history of ipsilateral renal stones, intraoperative perforation of the renal pelvis, and no tube drainage [ 4 ]. At present, there is no standard protocol for risk assessment of postoperative complications after PCNL and PN.…”
Section: Discussionmentioning
confidence: 99%
“…Hematuria is a severe life-threatening complication of these procedures, requiring timely treatment. Temporary clipping of the nephrostomy tube, application of hemostatic drugs, and blood transfusion are necessary conservative treatment measures [ 4 ]. It is recommended that angiography and embolization be performed by conservative treatment as early as possible in patients with severe hemorrhage [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%